2020
DOI: 10.3390/agriculture10100423
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer, and Volume Variations in Banana Slices during Convective Hot Air Drying: An Experimental Analysis

Abstract: Bananas are some of the most consumed fruits throughout the world, providing metabolizable calories and vitamins for humans, along with many other benefits. However, this fruit tends to be easily degraded by microorganisms and other chemical agents because of the high moisture content. Considering the importance, this work focuses on an experimental study regarding banana fruit drying. For such purpose, whole bananas were hand-peeled and sliced longitudinally and then dried by a hot air circulation oven with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…A phenomenon similar to that observed here was described by Farias et al. (2020) in the study of heat and mass transfer and volume variations in banana slices during convective drying.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A phenomenon similar to that observed here was described by Farias et al. (2020) in the study of heat and mass transfer and volume variations in banana slices during convective drying.…”
Section: Resultssupporting
confidence: 90%
“…To describe the behavior of the shrinkage rate of papaya slices during the drying process under different conditions, Equations ( 17) and ( 18), ( 19) and ( 20), ( 21) and ( 22) were fitted to the data of shrinkage of the control and probiotic-coated papaya slices, at temperatures of 50, 60 and 70°C, respectively, with a confidence interval of 0.95, Figure 2 shows that the volumetric shrinkage of papaya slices accompanies the drying rate, and a greater shrinkage was observed in the first hours of drying, being even more pronounced at temperatures of 70 and 60°C; after a period of high drying rate, the volumetric shrinkage tends to zero. A phenomenon similar to that observed here was described by Farias et al (2020) in the study of heat and mass transfer and volume variations in banana slices during convective drying. ( 14) A comparison between the probiotic-coated papaya slices and the control papaya slices showed that the probiotic coating of papaya slices led to a reduction in the volume shrinkage rate.…”
Section: Shrinkagesupporting
confidence: 87%
“…Initially, thermal stress undergoes swift escalation, and its maximum value (4.57 kPa) occurs at the instant when the temperature gradient reaches its peak. Subsequently, with the extension of the drying period, thermal stress gradually recedes as the temperature gradient declines (Farias et al, 2020). It is below 1.85 kPa after 60 min and below 0.34 kPa after 180 min.…”
Section: Resultsmentioning
confidence: 99%
“…(MR = 0.2) (n = 3 replicates) (Farias et al, 2020;Nguyen & Price, 2007). The moisture content is defined as the percentage on wet basis (%w.b.).…”
Section: Sample Preparation and Drying Kinetics Studymentioning
confidence: 99%
“…The structure inside PA banana is a non-porous solid material, so the moisture content relates to the structure while it is dried and there will not be a constant drying rate period like there would be with free water in connected pore space (de Lima, Farias Neto, & Silva, 2012;de Lima, Queiroz, & Nebra, 2002). In many previous studies (de Souza, de Andrade, & Rios, 2019;Farias et al, 2020;Maskan, 2000;Rahman, Ahmed, & Islam, 2018;Smitabhindu, Janjai, & Chankong, 2008;Thuwapanichayanan, Prachayawarakorn, & Soponronnarit, 2008), the drying of PA bananas has stopped microorganism activity when the final moisture content of PA banana is below 13%w.b. ; moreover, temperature and drying time are important parameters that affect the physical structure after drying.…”
mentioning
confidence: 99%